Towards a second republic : Irish politics after the celtic tiger - Kirby, Peadar (Pluto Press, 2011)
During the 1990s and 2000s, the Irish 'Celtic Tiger' model of development was hailed as a model for other European countries, but the global economic crisis has completely removed the credibility of Ireland's approach.